4-3x+5(2-x)=6(x+9)

Simple and best practice solution for 4-3x+5(2-x)=6(x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-3x+5(2-x)=6(x+9) equation:


4-3x+5(2-x)=6(x+9)

We simplify the equation to the form, which is simple to understand
4-3x+5(2-x)=6(x+9)

Reorder the terms in parentheses
4-3x+(+10-5x)=6*(x+9)

Remove unnecessary parentheses
+4-3x+10-5x=+6+*(+x+9+)

Reorder the terms in parentheses
4-3x+10-5x=+(+6x+54)

Remove unnecessary parentheses
+4-3x+10-5x=+6x+54

We move all terms containing x to the left and all other terms to the right.
-3x-5x-6x=+54-4-10

We simplify left and right side of the equation.
-14x=+40

We divide both sides of the equation by -14 to get x.
x=-2.85714285714

See similar equations:

| 5x+2-2x=8 | | 9n^2+16=-24n | | 5+5x=-50 | | 5x+-2-2x=8 | | 6(2x-1)-12=7+12(x+1) | | -0.875-(-n)=-0.583 | | m+6m+5m+8= | | 9=-5p+5+6p | | 4(2x+5)-18=36 | | -3=9p-9-8p | | (8)(16)=(6)(2x+6) | | 4=3p+6-2p | | -9x=-10x | | -3=-5p+9+6p | | 1-0.7k=1 | | -9=7p-15-6p | | 12xy^2+1=0 | | 24=5X-7 | | 3=3p-4-2p | | 17+9s=2(8s-3) | | 30-5(p-10)=11 | | 16x^2+3=-16x | | -14=4p+7-3p | | 6x+10=2y+10 | | -14=-8p+5+9p | | (x+1)/(2-x)*(2-x)^2/(x-2)*2/x+1 | | -11w+6=-38 | | .24.14= | | 10=-2p-2+3p | | -4=-4p-11+5p | | M/-16=-9 | | y-9=15(x-5) |

Equations solver categories